(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
The novel 2-thioxo-benzo[5,6]chromeno[2,3-d]pyrimidin-4-one derivatives were prepared by one pot multicomponent condensation reaction involving thiobarbituric acids, aromatic aldehydes and Î²-napthol in acetonitrile-water as solvent using surfactant, cetylpyridinium chloride (CPC) at water bath temperature in good yields. The structures of the compounds were confirmed by elemental analyses and spectral data.